2021
DOI: 10.21203/rs.3.rs-145846/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence of Under Nutrition and its Associated Factors Among Pregnant Women in Konso District, Southern Ethiopia: Community Based Cross Sectional Study

Abstract: Background: Under nutrition during pregnancy is an important public health problem. It is highly prevalent in Ethiopia but not sufficiently addressed yet. Hence, this study aimed to assess the prevalence of under nutrition and its associated factors among pregnant mothers in Konso district, Ethiopia. Methods: Community based cross-sectional study was conducted with qualitative inquiry study from December 2018 to January 2019. A multistage stratified sampling technique was used to select 527 subjects. Quantitat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The number of study participants per articles ranged from 195 to 1121. The prevalence of self-medication practice was reported from various regions in Ethiopia; three studies were from Amhara, 2,7,31 one from Addis Ababa, 5 four from Oromia, 15,25,32,33 one from South, 34 one from Tigray, 6 and one from Harari. 20 With regard to the sampling technique, six studies used simple random sampling, one study used systematic random sampling, two used multistage sampling techniques, one study used consecutive sampling, and one study used purposive sampling method Self-medication practice: The current meta-analysis showed that the overall prevalence of self-medication practice among pregnant mothers is 33.923 % (95% CI: 23.15-44.70, I² = 80.9%); (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…The number of study participants per articles ranged from 195 to 1121. The prevalence of self-medication practice was reported from various regions in Ethiopia; three studies were from Amhara, 2,7,31 one from Addis Ababa, 5 four from Oromia, 15,25,32,33 one from South, 34 one from Tigray, 6 and one from Harari. 20 With regard to the sampling technique, six studies used simple random sampling, one study used systematic random sampling, two used multistage sampling techniques, one study used consecutive sampling, and one study used purposive sampling method Self-medication practice: The current meta-analysis showed that the overall prevalence of self-medication practice among pregnant mothers is 33.923 % (95% CI: 23.15-44.70, I² = 80.9%); (Figure 2).…”
Section: Resultsmentioning
confidence: 99%